Report of accomplishments of the Director General - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The document Summary of the Director General's Report of Accomplishments provides informatin on important aspects of the institutional transformation process implemented during the period 1994-1998, and on the results and accomplishments of the technical cooperation carried out.